Prejudice in Naturalization Decisions: Theory and Evidence - Dragan Ilić (University of Basel, Center of Business and Economics (WWZ), 2016)
Immigrant groups that are marginalized in their host countries are disproportionately more likely to have their citizenship applications rejected. It is not readily obvious whether this disparity is due to prejudice on the part of decisionmakers or due to applicant differences in meeting naturalization standards. To address this question, I develop a simple model of a council deciding whether to grant applicants citizenship. The model implies an empirical test for relative prejudice using average applicant group rejection rates. Using Switzerland as a case study, I apply the test to newly collected data from six large municipalities. In five municipalities, the test cannot reject the hypothesis of no relative prejudice with respect to country of origin. The rejection pattern of the sixth municipality is consistent with prejudice. The model illustrates that the underlying mechanism in the decisionmaking process has bearing on the inference of prejudice from empirical data.
Keywords: 330